Analysis of Leadership Flexibility Capability of District/City Public Health Department in North Sumatra - Achmad Rifai; Purnawan Junadi; Endang Sulistyarini; Namora Lumongga Lubis (Faculty of Geography, Universitas Gadjah Mada, 2015)
Leadership has an important role in the organization as leader is in charge of supervising and controlling the course of an organization. Ability to lead in mobilizing and empowering employees will affect the performance of the organization. This behavior has a significant impact on the attitudes, behavior and performance of employees. The results of the study showed there is a significant relationship between characteristics such as age (p = 0.004), education(p = 0.034), work experience (p = 0.000), the experience of the organization (p = 0.000), and educational hierarchy (p =0.000) for leadership flexibility. Sex variable is not significant to the leadership flexibility (p = 0.801). There is a relationship with the flexibility of directive leadership style (p = 0.027), supportive leadership style (p = 0.046), and participative leadership style (p = 0.009) with the flexibility of leadership. There is aso a relationship between achievement-oriented leadership style and leadership flexibility (p = 0.000). There is a relationship between the individual characteristics of leadership style and versatility with variable: educational level of leadership (p = 0.021; OR = 19.265). The result suggests that we need more organized seminars / work shop / scientific studies that stimulate the realization of learning about leadership flexibility in improving the performance of the District/City Health Office and it is necessary to study theperformance of the head of the Department of Health assessment intensively and periodically